(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
Women, for a long time, were in small numbers in the prison system, but, starting in the 2000s, there was an exponential increase in the number of women incarcerated. This increase placed Brazil in third place in the global ranking of female prison population, with 46,604 women, according to data obtained in 2023. However, prisons were not planned for the female public, they are built by men and for men, which gives rise to several violations against incarcerated women, but little is addressed about this topic of great social and political relevance in the country. The aim is to answer the following question: how do violations occur during the process of incarceration of women in Brazil? This study uses the deductive approach method, bibliographic procedure methods, and indirect documentation as a research technique with data collected from public bodies. It is concluded that the State’s action in reformulating the Brazilian prison system, aimed at female specificities, is urgent. The systematic violations of human rights, especially those of imprisoned women, reveal not only the ineffectiveness of the system, but also its cruelty and inhumanity. Therefore, it is imperative that policies are implemented that respect the dignity and basic rights of all people deprived of their liberty, recognizing their specific needs and guaranteeing minimum conditions of health, hygiene and well-being. The fight for a fair and humanized prison system, also considering the peculiar conditions of the female gender, is essential for the construction of a more just and egalitarian society.